Butein effects in colitis and interleukin-6/signal transducer and activator of transcription 3 expression - Lee, Sehe Dong (World J Gastroenterol, 2015)
AIM: To evaluate the effects of butein on inflammatory cytokines, matrix metalloproteinase-9 (MMP-9), and colitis in interleukin (IL)-10(-/-) mice. METHODS: To synchronize colitis, 8- to 10-wk-old IL-10(-/-) mice were fed pellet-chow containing piroxicam for 2 wk. Subsequently, phosphate-buffered saline or butein (1 mg/kg per day, ip) was injected for 4 wk. Histologic scores, inflammatory cytokines, MMP-9 and phosphorylated signal transducer and activator of transcription 3 (pSTAT3) expressions were analyzed in IL-10(-/-) mice and in Colo 205 cells. RESULTS: Butein reduced the colonic inflammatory score by > 50%. Expression levels of IL-6, IL-1β, interferon (IFN)-γ and MMP-9 were decreased in the colons of mice exposed to butein, whereas other inflammatory cytokines (IL-17A, IL-21 and IL-22) were unchanged. Immunohistochemical staining for pSTAT3 and MMP-9 was significantly decreased in the butein-treated groups compared with the controls. Butein inhibited IL-6-induced activation of STAT3 in Colo 205 cells. CONCLUSION: Butein ameliorated colitis in IL-10(-/-) mice by regulating IL-6/STAT3 and MMP-9 activation.